Experimental setup of continuous ultrasonic monitoring for corrosion assessment - Suchato, Nutthawut; Kalashnikov, Alexander; Light, Roger; Sharples, Steve (2017)
The paper is devoted to the ultrasonic monitoring of accelerated corrosion. In order to achieve non-uniform corrosion (high surface roughness), passivation was applied to the corroding surface. A dedicated electronic multiplexed four channel front end was developed in order to feed the amplified waveforms from several transducers to the recording instrument. The experiment was conducted using two 5 MHz and two 10 MHz ultrasonic transducers all operating in the pulse echo mode. The transducers were excited in turn using gated bursts, and the received echoes were multiplexed and amplified before being digitized by a high accuracy ultrasonic instrument. Application of adaptive cross correlation to the recorded data allowed continuous thickness estimation of the non-uniformly corroded surface whilst cross correlation method gave unsatisfactory results.